2000
DOI: 10.1128/jvi.74.23.10994-11000.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Env-Independent Infection of Human CD4 Cells

Abstract: CD4− epithelial cells covering mucosal surfaces serve as the primary barrier to prevent human immunodeficiency virus type 1 (HIV-1) infection. We used HIV-1 vectors carrying the enhanced green fluorescent protein gene as a reporter gene to demonstrate that HIV-1 can infect some CD4− human epithelial cell lines with low but significant efficiencies. Importantly, HIV-1 infection of these cell lines is independent of HIV-1 envelope proteins. The Env-independent infection of CD4− cells by HIV-1 suggests an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…Therefore, it is possible that CXCR4 alone can mediate FIV infection, as suggested for the Petaluma strain (26,48). However, these results might also reflect the presence of an unidentified FIV receptor on CrFK cells or nonspecific cell entry that occurred through an envelope-independent mechanism, as has been reported for HIV (14,33). In addition to CXCR4, some FIV strains were also found to interact with primate CCR3 and CCR5.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, it is possible that CXCR4 alone can mediate FIV infection, as suggested for the Petaluma strain (26,48). However, these results might also reflect the presence of an unidentified FIV receptor on CrFK cells or nonspecific cell entry that occurred through an envelope-independent mechanism, as has been reported for HIV (14,33). In addition to CXCR4, some FIV strains were also found to interact with primate CCR3 and CCR5.…”
Section: Discussionmentioning
confidence: 50%
“…However, previous studies have shown that simian immunodeficiency virus (SIV) (6), HIV-2 (8,29), and some laboratory strains of HIV-1 (5,19,21) can also infect cells independent of CD4. Studies have also shown that a wide range of CD4-negative cells, including fibroblasts (36), epithelial cells (27), and neural cells (13), can be infected in vitro by certain strains of HIV. Further, it is well established that in vivo HIV can enter a wide range of cells that do not express CD4, including the cells of the nervous (12) and renal (9,28) systems.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Primarily Infectmentioning
confidence: 99%
“…Several molecules, including ICAM-1, LFA-1, MHCII, CD28, glycosaminoglycans, and glycosphingolipids, on the surface of the cell and virus have been shown to participate in HIV-1 infection, possibly by stabilizing virus-cell interactions or promoting postbinding events (3-6, 8, 9, 11-13, 32). Furthermore, HIV-1 infection independent of CD4 and chemokine receptors has been described, suggesting that novel receptors may be expressed on different cell types (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although CD4, chemokines, and their receptors are clearly important in the establishment of HIV infection, there is increasing evidence that additional surface molecules act as cofactors for binding and entry. Reports of primary HIV isolates that infect cell lines lacking CD4 and chemokine receptors suggest that there are uncharacterized accessory molecules that participate in infection (2)(3)(4)(5). In addition, HIV envelope, which is acquired as the virus particle exits the cell, includes proteins and lipids that are selectively obtained from the host membrane.…”
mentioning
confidence: 99%